전분 나노입자 첨가가 휘핑크림 품질특성에 미치는 영향 - 신혜영(Hye-Young Shin); 최희돈(Hee-Don Choi); 홍정선(Jung Sun Hong); 신경원(Kyeong Won Shin); 김종예(Jong-Yea Kim) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2020)
This study was performed to investigate how the addition of starch nanoparticles prior to whipping could affect the quality characteristics and stability of full-fat dairy cream. Starch nanoparticles were prepared by dry heating under mildly acidic conditions and added to dairy cream as amount of 1, 3, and 5% (w/w). The whipped cream's storage stability, viscosity, overrun, and droplet size were investigated in combination with various starch nanoparticle contents. The storage stability and apparent viscosity increased in parallel with the increasing starch nanoparticle content compared to the control. The mean size and homogeneity of the droplets in the whipped cream increased with higher starch nanoparticle addition levels. Even though the whipped cream overrun was reduced by the addition of starch nanoparticles, the 1% addition level exhibited a similar overrun value as the control.